1974
DOI: 10.1113/jphysiol.1974.sp010423
|View full text |Cite
|
Sign up to set email alerts
|

Plasma aldosterone, cortisol and corticosterone concentrations in the new‐born guinea‐pig

Abstract: 4. There was no constant relation between aldosterone and glucocorticoid concentrations in the animals studied, either new-born or adult.5. Plasma cortisol: corticosterone ratios were not constant but varied considerably. In the adult a sevenfold rise in plasma cortisol concentration occurred under certain conditions without any change in plasma corticosterone concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…It was shown that at the end of pregnancy the concentration of plasma aldosterone was increased (Beitins et al, 1972;Malinowska and Nathanielsz, 1974] which is in accord ance with our finding of a greater width of the zona glomerulosa at this stage. The trauma of parturition, loss of fluid, minimal hemorrhagia, as well as high levels of angiotensin I could be responsible for the enlargement of the zona glomerulosa noted in the early postpartum period [Beitinset al, 1972;Yates et al, 1974;Mott, 1975;Lammintausta et al, 1977].…”
Section: Discussionsupporting
confidence: 81%
“…It was shown that at the end of pregnancy the concentration of plasma aldosterone was increased (Beitins et al, 1972;Malinowska and Nathanielsz, 1974] which is in accord ance with our finding of a greater width of the zona glomerulosa at this stage. The trauma of parturition, loss of fluid, minimal hemorrhagia, as well as high levels of angiotensin I could be responsible for the enlargement of the zona glomerulosa noted in the early postpartum period [Beitinset al, 1972;Yates et al, 1974;Mott, 1975;Lammintausta et al, 1977].…”
Section: Discussionsupporting
confidence: 81%
“…Some other reports on cortisol levels in conscious, non-stressed guinea-pigs have given values lower thati those in this study. Blood cortisol concentrations in the present study were 19-3 /u,g/100 ml for males and 31-8 fig/100 ml for females compared with Malinowska and Nathanielsz's (1974) value for male plasma of 8-4 /Ag/100 ml and that of Fazekas, Homoki and Teller (1974) of 7-5 fig/lOO ml plasma for males and 12-6 /i,g/100 ml plasma for females. Speculative reasons for this discrepancy in cortisol values could include genetic differences in corticosteroid synthesis or metabolism, as has been demonstrated in guinea-pigs by Burstein, Kimbal and Bhavnani (1963) or strain differences in plasma corticosteroid-binding capacity as has been mentioned in the review by Shire (1974).…”
Section: Disgussionmentioning
confidence: 70%
“…three times that found for man. Malinowska and Nathanielsz (1974) found a mean plasma aldosterone concentration of 7-2 ng/100 ml in four conscious, non-stressed, adult, male guineapigs. In the present study (Table 2), sodium loading produced levels comparable with those in their report.…”
Section: Disgussionmentioning
confidence: 99%
“…trypsin, pepsin and ovalbumin standards (Sig ma) were used. Concentrations of albumin in maternal scrum were determined by a brontocresol green dye binding method 110] and of corticosterone and insulin by a binding protein [9] and radioimmunoassay tech nique. respectively [3],…”
Section: Chemical Assaysmentioning
confidence: 99%